2022
DOI: 10.1186/s12876-022-02525-1
|View full text |Cite
|
Sign up to set email alerts
|

The CT-based intratumoral and peritumoral machine learning radiomics analysis in predicting lymph node metastasis in rectal carcinoma

Abstract: Background To construct clinical and machine learning nomogram for predicting the lymph node metastasis (LNM) status of rectal carcinoma (RC) based on radiomics and clinical characteristics. Methods 788 RC patients were enrolled from January 2015 to January 2021, including 303 RCs with LNM and 485 RCs without LNM. The radiomics features were calculated and selected with the methods of variance, correlation analysis, and gradient boosting decision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the present study, radiomics signature of NCE-CT did not have a statistically significant difference from that of the CE-CT in the validation cohort (AUC, 0.676 vs 0.711, p=0.187). Yuan et al (21) recruited 788 patients with RC to construct a CT-based radiomics analysis to predict LNM in RC. It was found that there were no statistical significances of the intra-tumoral Bayes model among the non-enhanced, arterial or venous-phase CT in the training and validation cohorts, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, radiomics signature of NCE-CT did not have a statistically significant difference from that of the CE-CT in the validation cohort (AUC, 0.676 vs 0.711, p=0.187). Yuan et al (21) recruited 788 patients with RC to construct a CT-based radiomics analysis to predict LNM in RC. It was found that there were no statistical significances of the intra-tumoral Bayes model among the non-enhanced, arterial or venous-phase CT in the training and validation cohorts, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These three algorithms have advantages not only in small sample data processing and avoiding overfitting, but also in computing power requirements. Their performance has been verified by many studies [ 26 28 ]. In this research, the LR model achieved the highest AUC, specificity, and sensitivity, meeting the requirements for the detection of occult fractures in clinical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 84%
“…This process ultimately results in a predictive or prognostic model based on extracted radiomic features and can be applied to any clinical endpoint. Although the methodology behind radiomics is rapidly evolving, several contemporary studies have highlighted the enormous potential of radiomics in a variety of diseases, including, but not limited to, cancers of the gastrointestinal tract [ 4 , 5 ], lung [ 6 ], brain [ 7 ], and genitourinary tract [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%